会话分析 ：马来西亚华语会话中“哦”的 功能与使用情况 = Conversation analysis : a study of the functions and usages of “O” in spoken Malaysia Mandarin - 黄丽诗 Ng, Yi Ting (2016)
在日常的华语会话中，交际者常会用“哦”、“啊”、“嗯”等标记来作为回应，或用来表达自己情感。然而，目前学术界对“哦”的研究并不完整。另外，“哦”在日常会话的使用情况以及功能并不与词典和教科书相符。《马来西亚华语会话中“哦”的使用情况与功能》采用会话分析的方法，旨在探讨马来西亚男女青年在日常会话中如何使用“哦”来表达他们的言语，从而研究“哦”更多的功能以及使用情况。“哦” 可以念成阳平声(“哦↗”)或去声（“哦↘”），在前辈的研究下，不同声调的“哦”都拥有不同的功能。“哦↗”在《辞海》里可以表示领会，“哦↘”则是表示惊讶。部分语法书把“哦”作为感叹词，其意义可能会随着声调的转变而不同。另外，教科书如《初中统考华文语文知识》则认为“哦”只能表达疑惑。本文会从所收集到的语料去探讨“哦”的语用功能，旨在研究“哦”在马来西亚华语会话中更多的功能和使用情况，并分析“哦”的功能和使用情况是否会随着声调的不同而改变。是次研究将“哦”的功能分为认知转变标记以及非认知转变标记。当“哦”成为认知转变标记时，它可以出现于这四类的使用情况：第三位置结序（62%）、引发修补（8%）、自我唤起记忆（14%）以及自我明白（6%）。笔者将“哦”的其他功能归于非认知转变标记，它们分别是表达同意对方观点（6%）和引述他人说话的标记（4%）。本文旨在让读者能对马来西亚华语会话中“哦”的功能和使用情况有更深入且全面的理解。另外，笔者也希望本文能填补相关研究中的空缺部分，为华语会话研究尽一份绵力。In casual Mandarin conversation, speakers use discourse markers like “o”, “hmm”, “ah” as reply, or use these as a way to express themselves. However, the existing research about “o” is limited and uncomplete. Moreover, the actual usages and functions about “o” are not synchronize with the dictionaries and local text book. This study aims to provide better understanding of how “o” is used by Malaysian Chinese, in terms of context and the functions it has. “O” (哦) can be pronounced by using the second tone (“o↗”) or the forth tone (“o↘”) in Mandarin language. According the previous research, each researcher has different perspective towards “o”, in either two tones. In the official Mandarin dictionary “Ci Hai”（《辞海》）, the meaning of “o↗” displays an understanding response of speaker and “o↘” indicates a surprising response of speaker. However, some Chinese grammar books define “o” as an interjection (感叹词), the meaning of it might change whenever the tone is different. Furthermore, local text books such as “Chu zhong tong kao hua wen yu wen zhi shi” （《初中统考华文语文知识》）claims that “o” can only represent as a doubting response of speaker. Beyond the findings of previous research, this paper demonstrated extended functions and usages of “o”. Nevertheless, in contrast with most past findings about the independent functions for respective tones, this paper advocates that different tones of “o” may share some common functions. The function of “o” can be understood by change-of-state token or non-change-of-state token. In a change-of-state token, it can be used in following context: sequence closing third (62%), repair initiator (8%), self-remembering (14%) and self-understanding (6%). Other functions such as showing agreement (6%) and indicating others’ saying (4%) are categorized as non-change-of-state token in the paper.This paper will use the actual data from participants’ recorded conversation and transcribe it for analysis purpose, and to further understand the usages and functions of “o” in spoken Malaysia Mandarin.